Siwa Nataraja Sebagai Landasan Filosofis Dalam Penciptaan Karya Seni Tari - Ni Made Ayu Dwi Oktaviani; I Wayan Rudiarta (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This study aims to describe the vital position of Shiva Nataraja as a source of inspiration in the creation of dance artworks. Referring to the phenomenon that many dance artworks, especially Balinese dances are staged in the implementation of a religious ceremony, it indicates that there is a spiritual aspect that animates a dance, and the cosmic dance of Lord Shiva, known as Shiva Nataraja, is seen as the source of his inspiration. This research was conducted qualitatively with the method of literature study. Data was collected through various literatures which were then analyzed through data collection, condensation, presentation, and data verification. The results of the analysis provide research findings that the philosophy of creating dance artworks originates from the concept of pancakrtya as the five activities of God and consists of srihti, sthiti, samhara, tirabhava and anugraha. These five activities that take place repeatedly lead to the emergence of basic standards in Balinese dance such as agem, tandang, tangkis, tangkep and others.